Immobilization of Beta Galactosidase for production of fermented milk products with low lactose - Geetha R (Department of Dairy Science, College of Veterinary and Animal Sciences, 1996)
An immobilized β – galactosidase enzyme system was developed using permeabilized cells of K. fragilis as an enzyme source and food grade agar as the immobilizing agent. This was utilised for hydrolysing lactose content present in milk, which in turn was used for preparing selected fermented products with low lactose content. An attempt was also made to assess the possibility of utilisation of whey as a medium for culture maintenance with a view to utilise the by – product. A detailed review of literature has been presented about β – galactosidase specific activity of different organisms, various immobilization techniques,influence of lactose hydrolysis on physico chemical properties of the product and also about the utilisation of whey as a media for culture maintenance. The experiment comprised of determination of β – galactosidase specific activity of permeabilized cells of three selected organisms and assessing the suitability of agar and sodium alginate as immobilizing agents. Since β – galactosidase specific activity was found to be the highest for K. fragilis, it was selected as the best enzyme source. Agar was selected as the suitable immobilizing agent because it was found to be safe, economical and comparatively more efficient. Using these two raw materials an efficient immobilized enzyme system was developed and its efficiency was assessed by estimating the rate of lactose hydrolysis at fixed time intervals. Selected strains of starter bacteria were screened for their performance in four different media viz. Skim milk, 50 per cent lactose hydrolysed skim milk, condensed whey, and 50 per cent lactose hydrolysed condensed whey. Two media were selected from among the four, which stimulated the starter activity and used for further studies. Three different products viz., yogurt, bifidus yogurt and acidophilus milk were prepared using 50 per cent lactose hydrolysed milk obtained by passing through the immobilized enzyme system and cultures maintained separately in lactose hydrolysed milk and lactose hydrolysed whey. Two control products were prepared with ordinary milk and above described cultures. All the three products under different treatments were analysed for acidity, pH, tyrosine value, total lactic count and sensory evaluation. The results obtained in the study were compared with similar reported findings and the following conclusions were made. 1. Permeabilized cells of K. fraglis possessed better B – galactosidase specific activity than the cells of S. thermophiles and L. delbrueckii sub sp. bulgaricus. 2. Food grade agar was found to be an efficient immobilizing agent than sodium alginate. 3. The immobilized enzyme prepared with 10 g of K. fragilis could hydrolyse 50 per cent of lactose content present in 250 ml of milk, after holding in the column for four hours at room temperature (300 C). 4. The rate of lactose hydrolysis was found to be the maximum within first half an hour, thereafter a decline in the rate of hydrolysis was observed. 5. This system was repeatedly used in five batches without any change in its efficiency or mechanical stability of the beads but after which a reduction in activity was noticed. 6. A slight brownish discolouration was observed on the beads when the column was stored for a long period. 7. Repalcement of skim milk with whey was a starter media slightly enhanced the activity of cultures, especially, S. thermophilus, L. lactis and B. bifidum whereas L. acidophilus and L. delbrueckii sub sp. bulgaricus performed better in skim milk, especially when the media was subjected to lactose hydrolysis. 8. The utilisation of lactose hydrolysed milk for preparation of products slightly enhanced the acidity, proteolytic activity and viable cell count of yogurt, bifidus yogurt and acidophilus milk. 9. In the case of treatment yogurts (Y1 and Y2) prepared with lactose hydrolysed milk, a significantly higher protolytic activity was observed. 10. Organoleptic evaluation indicated that the utilisation of lactose hydrolysed milk and cultures maintained in lactose hydrolysed skim milk and whey did not affect the flavour and textural characteristics of yogurt. On the contrary the flavour as well as body and texture scores of bifidus yogurt and acidophilus milk were slightly improved by this technique.